Research on MIX-based anonymous communications - LU Tian-bo; CHENG Xiao-ming; ZHANG Bing (Tongxin xuebao)
Privacy and anonymity on the Internet are gaining increasing attention from both the scientific and the large Internet user community in recent years.Privacy does not only mean the confidentiality of information,but also mean not revealing who is communicating with whom,and how often.After describing the technology of MIX,a survey of ano-nymity technologies based on it was given.Finally WonGoo,a scalable and practical decentralized peer-to-peer protocol was presented that provides strong anonymity and high efficiency with layered encryption and random forwarding.